EDUKASI PROGRAM LATIHAN FISIOTERAPI PADA PENDERITA STROKE DI RS EFARINA BERASTAGI - Muliati, Muliati; Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; Rodearni Damanik (Nusantara Hasana Journal, 2024)
Stroke is a leading cause of disability and death worldwide, including in Indonesia. Stroke patients often experience impaired motor and sensory function, as well as limitations in daily activities, requiring ongoing rehabilitation treatment. Physiotherapy plays a crucial role in improving the quality of life of stroke patients through structured and ongoing exercise programs. This community service activity aims to provide education about physiotherapy exercise programs to stroke patients at Efarina Hospital in Berastagi. The methods used include counseling, exercise demonstrations, and direct support for patients and their families. The results of the activity indicate an increase in patient and family understanding of the importance of physiotherapy exercises and increased participation in independent exercise. Thus, the education provided can optimally support the rehabilitation process for stroke patients.